The postoperative management of pain from intracranial surgery in pediatric neurosurgical patients. Issue 7 (July 2014) - Shay, Joanne E.; Kattail, Deepa; Morad, Athir; Yaster, Myron; Soriano, Sulpicio
Summary Pain following intracranial surgery has historically been undertreated because of the concern that opioids, the analgesics most commonly used to treat moderate‐to‐severe pain, will interfere with the neurologic examination and adversely affect postoperative outcome. Over the past decade, accumulating evidence, primarily in adult patients, has revealed that moderate‐to‐severe pain is common in neurosurgical patients following surgery. Using the neurophysiology of pain as a blueprint, we have highlighted some of the drugs and drug families used in multimodal pain management. This analgesic method minimizes opioid‐induced adverse side effects by maximizing pain control with smaller doses of opioids supplemented with neural blockade and nonopioid analgesics, such nonsteroidal antiinflammatory drugs, local anesthetics, corticosteroids, N‐methyl‐D‐aspartate (NMDA) antagonists, α2‐adrenergic agonists, and/or anticonvulsants (gabapentin and pregabalin).